Parallel Distribution Channels-source of Internal Conflict - Zameer, Asif (Indian Journal of Marketing, 2006)
Many consumer good companies who are basically into retail sales have a substantial market in institutions to justify setting up of an institutional sales group. Examples in India are-Gillette, Dabur, Lakhanpal (Novino), Blow Plast (VIP Luggage), and Luxor-Parker etc. With my first hand experience of either working or interacting with many such companies, I can say that there is an underlying tussle and sometimes even contentious relationship between the retail and institutional sales force. This conflict many times flares up into arguments and accusations. It is not suggested that this is a serious problem universally. The companies with established systems have evolved mechanisms to avoid such unhealthy conflict or deal with it at the branch level itself so that it is not a regular irritant. However, for companies who are new to operating parallel distribution systems, such a conflict can build up and cause harm to the overall interests. The top management can do well to recognize the telltale signs of such a conflict, which are going to be talked about later in this article, and proactively implement measures to control it.